Catatonia and Cognitive Impairments: A Systematic Review - Serrat, Francesc; Iglesias-Gónzalez, Maria; Sanagustin, David; Etxandi, Mikel; de Pablo, Joan; Cuevas-Esteban, Jorge (Frontiers in Psychiatry, 2022)
Background: Catatonia is an underdiagnosed and undertreated neuropsychiatric syndrome characterized by catalepsy, negativism, mutism, muscular rigidity, and mannerism, often accompanied by autonomic instability and fever. Although there is growing interest in studying cognitive impairments before and after catatonia, little is known about the cognitive features of the syndrome. Methods: This systematic review was registered at PROSPERO (CRD42022299091). Using a PRISMA approach, we searched Pubmed, ScienceDirect and PsycArticles using a combination of the terms ‘Catatonia’ and ‘Cognitive impairment’ and ‘Executive function’ and ‘Frontal lobe’ and ‘Parietal lobe’. Studies included original research articles enrolling patients with catatonic syndrome according to specified criteria. Fourteen studies were deemed relevant for inclusion. The abstraction form included age, assessment during acute episode, associated diagnosis, assessment procedure and cognitive domains. Outcome measures were extracted. Results: Executive functions and visuospatial abilities proved to be the most investigated domains. A great heterogeneity has been observed in the assessment tools used among the fourteen evaluated studies. Findings showed that catatonic patients had worse performance than healthy and non-catatonic psychiatric patients in frontal and parietal cortical functions. Conclusion: Because of the small number of studies in such heterogeneous areas and significant methodological limitations, the results should be regarded with caution. Future research assessing cognitive impairments on catatonic patients is needed.